Peutz-Jeghers syndrome: diagnostic and therapeutic approach - Kopacova, Marcela; Tacheci, Ilja; Rejchrt, Stanislav; Bures, Jan (World journal of gastroenterology, 2009)
Peutz-Jeghers syndrome (PJS) is an inherited, autosomal dominant disorder distinguished by hamartomatous polyps in the gastrointestinal tract and pigmented mucocutaneous lesions. Prevalence of PJS is estimated from 1 in 8300 to 1 in 280,000 individuals. PJS predisposes sufferers to various malignancies (gastrointestinal, pancreatic, lung, breast, uterine, ovarian and testicular tumors). Bleeding, obstruction and intussusception are common complications in patients with PJS. Double balloon enteroscopy (DBE) allows examination and treatment of the small bowel. Polypectomy using DBE may obviate the need for repeated urgent operations and small bowel resection that leads to short bowel syndrome. Prophylaxis and polypectomy of the entire small bowel is the gold standard in PJS patients. Intraoperative enteroscopy (IOE) was the only possibility for endoscopic treatment of patients with PJS before the DBE era. Both DBE and IOE facilitate exploration and treatment of the small intestine. DBE is less invasive and more convenient for the patient. Both procedures are generally safe and useful. An overall recommendation for PJS patients includes not only gastrointestinal multiple polyp resolution, but also regular lifelong cancer screening (colonoscopy, upper endoscopy, computed tomography, magnetic resonance imaging or ultrasound of the pancreas, chest X-ray, mammography and pelvic examination with ultrasound in women, and testicular examination in men). Although the incidence of PJS is low, it is important for clinicians to recognize these disorders to prevent morbidity and mortality in these patients, and to perform presymptomatic testing in the first-degree relatives of PJS patients.
Keywords: Peutzův-Jeghersův syndrom; Male; Endoscopy, Gastrointestinal; Polyps; polypy; Adolescent; Child; Intestine, Small; dítě; Adult; Aged; dospělí; Gastroenterology; mužské pohlaví; senioři; mladiství; gastroenterologie; Endoscopy; lidé; Peutz-Jeghers Syndrome; ženské pohlaví; Humans; střevní nádory; Intestinal Neoplasms; tenké střevo; Hamartoma; endoskopie; Female; gastrointestinální endoskopie; lidé středního věku; hamartom; Middle Aged